Predicting some quality factors of annual ryegrass (Lolium multiflorum lam.) by means of spectral reflectance values - í–zyiğit, Yaşar; Aydinoğlu, Bilal (Cellular and Molecular Biology, 2018)
This study was conducted to predict some quality factors of the annual ryegrass (Lolium multiflorum Lam.) with spectral reflectance values in the Forage Crops Laboratory in the Department of Field Crops at the Agriculture Faculty, Akdeniz University, Turkey. In the study, variations resulting from different implementations (moisture level, bale density, propionic acid application and storage period) made during haymaking were determined with reflectance values. For reflectance measurements, a portable spectroradiometer and a contact probe (plant probe) were used and predicting models were created. Results of this study showed that quality factors of dried Annual ryegrass could be predicted with reflectance values, and that reflectances had higher efficacy in the red region for, the red and green, and the NIR region for crude protein, crude ash and crude cellulose, respectively. The results reveal that in dried annual ryegrass, there are significant relationships between feed quality factors such as crude protein, crude ash and crude cellulose, and reflectance values, and that especially crude protein levels can be rapidly and cheaply predicted by using reflectance values.